Analisis dan Optimasi Pengaruh Suhu Gas Umpan Pada Kinerja Acid Gas Removal Unit - Iwan Febrianto; Nelson Saksono (UM Purwokerto Press, 2021)
The Gas Gathering Station (GGS) in field X processes gas from 16 (sixteen) wells before being sent as selling gas to consumers. The sixteen wells have decreased in good pressure since 2011, thus affecting the performance of the Acid Gas Removal Unit (AGRU). The GGS consists of 4 (four) main units, namely the Manifold Production/ Test, the Separation Unit, the Acid Gas Removal Unit (AGRU), the Dehydration Unit (DHU). The AGRU facility in field X is designed to reduce the acid gas content of CO2 by 21 mol% with a feed gas capacity of 85 MMSCFD. A decrease in reservoir pressure caused an increase in the feed gas temperature and an increase in the water content of the well. Based on the reconstruction of the design conditions into the simulation model, the amine composition consisting of MDEA 0.3618 and MEA 0.088 wt fraction to obtain the percentage of CO2 in the 5% mol sales gas. The increase in feed gas temperature up to 146 F caused foaming due to condensation of heavy hydrocarbon fraction, so it was necessary to modify it by adding a chiller to cool the feed gas to become 60 F. Based on the simulation, the flow rate of gas entering AGRU could reach 83.7 MMSCFD. There was an increase in gas production of 38.1 MMSCFD and condensate of 1,376 BPD. Economically, the addition of a chiller modification project was feasible with the economical parameters of NPV US 132,000,000, IRR 348.19%, POT 0.31 year and PV ratio 19.06.